Characterizing sintered nano-hydroxyapatite sol-gel coating deposited on a biomedical Ti-Zr-Nb alloy - Jafari, H. (Springer New York LLC, 2016)
In this study, sol-gel dip-coating method was used to coat nano-hydroxyapatite on specimens of Ti-14Zr-13Nb alloy for orthopedic applications. The coated specimens were sintered at three different temperatures and time spans to evaluate the impact of sintering process on microstructure, mechanical, bio-corrosion, and bioactivity properties of the coating. Field-emission scanning electron microscopy and x-ray diffraction were used to analyze the coating microstructure. Coating adhesion and mechanical performance were also investigated by scratch testing. Besides, electrochemical corrosion and immersion tests were performed in simulated body fluid to examine the sintering effect on corrosion performance and bioactivity of the coatings, respectively. The evaluations of coated specimens displayed that sintering at elevated temperatures leads to higher surface integrity and improves crystallinity of the nano-hydroxyapatite to approximately 89% which brings about distinctively enhanced mechanical properties. Similarly, it improved the corrosion rate for about 17 times through sintering at 700Â Â°C. Immersion test proved that the coating increased the bioactivity resulted from the dissolution of calcium phosphates into the corresponding environment. It is noticeable that sintering the dip-coated specimens in the nano-hydroxyapatite improves corrosion performance and maintains bioactive behaviors as well.